Exploring the Diagnostic Performance of Magnetic Resonance Imaging in Ultrasound-Guided High-Intensity Focused Ultrasound Ablation for Abdominal Wall Endometriosis - Hu, Shangying; Liu, Yuhang; Chen, Rongsheng; Xiao, Zhibo (Frontiers in Physiology, 2022)
Objective: This study aimed to explore the clinical value of magnetic resonance imaging (MRI) combined with ultrasound-guided high-intensity focused ultrasound (USg-HIFU) for the diagnosis and treatment of abdominal wall endometriosis (AWE). Methods: MRI was performed before and after USg-HIFU. Information on clinical characteristics of patients, MRI characteristics of lesions, and treatment outcomes were collected. Thirty AWE lesions in 29 patients were examined before HIFU treatment, while 27 patients were examined after treatment. The results of MRI and color doppler ultrasound before surgery, as well as the volume and the apparent diffusion coefficient (ADC) values of the lesions before and after USg-HIFU treatment were compared. We also observed the clinical symptoms remission, recurrence, and ablation rates of the lesions in follow-up after HIFU treatment. Results: The locations of the 30 AWE lesions were identified by MRI before USg-HIFU treatment. Their sizes appeared larger on MRI than ultrasound (P<0.05). A total of 27 lesions were evaluated by MRI after USg-HIFU treatment, of which 92.6% (25/27) lesions were of high or slightly high signal intensity on T1-weighted images, and 77.8% (21/27) lesions were of mixed signal intensity on T2-weighted images. The mean ADC values of AWE lesions were 1.47 (1.20–1.59) ×10-3 mm2/s and 1.86 (1.61–2.12) ×10-3 mm2/s for pre-and post-HIFU treatment (P<0.05). Patients with higher ablation rates (>50%) had a higher complete/partial remission rate than those with lower ablation rates (<50%), and had a lower recurrence rate (P<0.05). Conclusions: MRI is a useful tool for identifying the location, size, and concurrent changes of AWE before and after USg-HIFU treatment, which is beneficial for follow-up monitoring and defining treatment efficacy.